Trans Metro Pekanbaru (TMP) Sebagai Moda Pilihan Transportasi Umum Massal - Fariz Anzhari Kwanda; Muhammad Reza; Aryo Sasmita (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
The increasing amount of transportation has a negative impact in the form of air pollution. One of the mass transportation that is often used in Pekanbaru City is the Trans Metro Bus. The purpose of this study was to analyze the passengers who switched or shifted from private vehicles to the Trans Metro Pekanbaru. Lemeshow method to determine the number of research samples with a questionnaire to passengers who switch or shift to Trans Metro Pekanbaru. The results of this study are the characteristics of respondents based on the highest age Pekanbaru, namely age 21-30 years as much as 36.67%, the characteristics of respondents based on the highest sex male sex as much as 52.5%, the characteristics of respondents based on the highest occupation, namely private employees and civil servants as much as 30.83%, the characteristics of respondents based on the highest travel destination, namely schools as much as 35.83%, and the characteristics of respondents based on the transition of private vehicles to Trans Metro Pekanbaru the highest, namely motorbikes as many as 88 vehicles with a percentage of 73 , 33%.Keywords: Mass transportation, Trans Metro Pekanbaru